An international study of high school teachers’ experience of incorporating water resources in their teaching - Kwee, Ching Ting Tany; Dos Santos, Luis Miguel (Frontiers in Education, 2023)
This study aims at investigating the significant factors influencing teachers’ motivations for incorporating water resources in their teaching. By exploring teachers’ experiences of teaching water resources in their Education for Sustainable Development (ESD) classroom, this study has identified the significant personal and contextual factors influencing teachers’ motivation, thereby closing the research gap on the paucity of research on teachers’ motivation in teaching water resources within the realm of ESD. Based on the purpose of the study and the social cognitive career theory, this study is guided by two research questions: 1) How do teachers describe their experience of incorporating water resources in their classrooms? 2) Why are teachers motivated to incorporate water resources in their teaching? The Interpretative Phenomenological Analysis with the semi-structured interviews and focus group discussions was employed to recruit ten participants internationally. The results indicated that personal beliefs and characteristics of the community played significant roles in their experiences and motivations. This study’s findings can provide insights into how and why teachers’ personal beliefs and contextual variables like geographic and cultural influences can encourage teachers to implement water resources elements in their teaching, thereby illuminating the possible responsive pedagogies for successful cross-disciplinary ESD in future.